Discussion spaces and legitimization processes of movement education: The case of the XV Pan-American Physical Education Congress, Peru 1995 - Scharagrodsky, Pablo (2022)
This articles analyzes, from a qualitative approach, the 1995 Pan-American Physical Education Congress taken place in Peru as a space for socialization, dissemination of knowledge, sharing of theoretical perspectives, as well as space of legitimization for some experts, influence and power for some international organizations. The article seeks to understand how knowledges, experts and organizations validate certain “true” meanings that conceptualize the vast universe of physical culture, physical education and sports. The interpretative examination focuses in various documentary sources, such as minutes and memories of the Congress, presentations by experts, the subjects of the presentations, and memories of other Pan-American congresses. Additionally, the study includes semi-structured interviews to organizers and attendees.